2020
DOI: 10.1038/s41598-020-73094-0
|View full text |Cite
|
Sign up to set email alerts
|

An association study of C9orf3, a novel component of the renin-angiotensin system, and hypertension in diabetes

Abstract: The renin-angiotensin system (RAS) is important in the onset and course of cardiovascular, kidney, and metabolic disorders. Previous reports showed that the RAS blockade protects organs and suppress the development of type 2 diabetes mellitus. A novel component of the RAS, namely, chromosome 9 open reading frame 3 (C9orf3), was recently identified, however, its effects are unclear. We evaluated whether the genetic variant of C9orf3 is associated with morbidity of hypertension among subjects with type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…This may reflect the fact that these genes are more likely to play a critical role for dystonia pathogenesis during brain development and less so in the adult mature brain 30 . Single‐nucleotide polymorphism‐based association studies have shown that more common variations in AOPEP may influence susceptibility to prevalent disease traits, such as arterial hypertension, polycystic ovary syndrome, and atrial fibrillation 31‐33 . We believe, however, that it is currently not possible to bring these observations into a direct pathophysiological context with dystonia because the herein identified loss‐of‐function alterations are likely to have molecular consequences different from those encountered in association to common (non‐neurological) disease risk alleles.…”
Section: Discussionmentioning
confidence: 91%
“…This may reflect the fact that these genes are more likely to play a critical role for dystonia pathogenesis during brain development and less so in the adult mature brain 30 . Single‐nucleotide polymorphism‐based association studies have shown that more common variations in AOPEP may influence susceptibility to prevalent disease traits, such as arterial hypertension, polycystic ovary syndrome, and atrial fibrillation 31‐33 . We believe, however, that it is currently not possible to bring these observations into a direct pathophysiological context with dystonia because the herein identified loss‐of‐function alterations are likely to have molecular consequences different from those encountered in association to common (non‐neurological) disease risk alleles.…”
Section: Discussionmentioning
confidence: 91%
“…Even though this prediction highlights the potential variability caused by rs2767403, the AOPEP gene encodes a metallo protease linked to the renin-angiotensin system [47]. In particular, it is able to cleave angiotensin III (but not I and II) to generate Angiotensin IV.…”
Section: Analysis Of Single Snpsmentioning
confidence: 97%
“…Twenty-one and 24 T2D- associated variants overlapped ER stress- or cytokine-specific opening CREs, respectively (Figure 4A; Supplementary Table 5) . Among these, 11 variants overlapped ER stress-specific opening CREs that are within 500kb of an ER stress response gene (Figure 4B; Supplementary Table 5), including AOPEP - a key gene involved in peptide processing 70 and robustly induced by ER stress in beta cells (Figure 4C; Supplementary Tables 2-3) . We detected an ER stress-specific induced CRE in the AOPEP intron, which harbors the T2D-associated variant rs4744423 (Figure 4D; Supplementary Tables 4-5) .…”
Section: Resultsmentioning
confidence: 99%